Upaya Meningkatkan Kecerdasan Emosi dan Pengendalian Diri Peserta Didik Melalui Penggunaan Metode Curah Pendapat dan Tanya Jawab di Kelas VIII SMP Negeri 19 Kota Bogor - Margarita, Sindi (Journal of Social Studies Arts and Humanities (JSSAH), 2023)
EFFORTS TO INCREASE EMOTIONAL INTELLIGENCE AND SELF-CONTROL OF STUDENTS THROUGH THE USE OF BRAINSTORMING AND QUESTION AND ANSWER METHODS IN GRADE VIII JUNIOR HIGH SCHOOLS (SMP NEGERI 19 KOTA BOGOR) The purpose of this study was to determine the increase in Emotional Intelligence and Self-Control of students in class VIII junior high school through the use of Brainstorming and Question and Answer Methods. The method used is the counseling guidance action research method which consists of two cycles. In cycle I guidance counseling services were carried out using the Brainstorming and Question and Answer Method while in cycle II using the Improved Brainstorming and Question and Answer Method. In each cycle consists of four stages of research namely planning, implementation of action, observation, and reflection. The research data were analyzed using a comparative descriptive followed by reflection. Comparative descriptive is done by comparing the initial condition data, cycle 1 and cycle 2, both for learning outcomes. The results of this study indicate that: First, the use of Brainstorming and Question and Answer Methods can improve students' Emotional Intelligence and Self-Control. It is proven that the percentage of the results of the questionnaire increased the Emotional Intelligence and Self-Control of students who experienced an increase from the initial condition of the average daily test score of 71.95 in cycle I to 76.38 and in cycle II to 81.46 or in the final condition it increased by 13 .22% of initial conditions. It is proven that the percentage of completeness in the results of the Questionnaire to increase the Emotional Intelligence and Self-Control of students increased from the initial conditions of 64.86% in cycle I to 86.49% in cycle II or in the final conditions it increased by 33.35% from the initial conditions.